The 18 Challenges of Leadership: A Practical, Structured Way to Develop Your Leadership Talent - Trevor Waldock (London ; New York Pearson Prentice Hall, 2004)
This is the first book to simply identify the core challenges faced by all leaders, provide a easy way of assessing yourself against each of these challenges and suggesting the actions that will make you a better, more effective leader.
Keywords: Leadership; Executives; Nonfiction